Hearing the roar: Spectator noise and umpires stress in major badminton tournaments - Sjödin, F.; Felder, H.; Holmström, S.; Fahlström, M. (International Journal of Racket Sports Science, 2023)
This study investigates the effects of spectator noise on umpire stress levels during major badminton tournaments. Previous research has shown that spectator noise can affect performance and decision-making in sports, including badminton. However, there is limited understanding of how this phenomenon explicitly affects umpires, who play a crucial role in officiating matches. Nine experienced umpires from the 24th Badminton World Federation (BWF) World Championships participated in the study. Heart rate variability (HRV) was used to measure stress levels objectively. In addition, subjective noise sensitivity and general stress levels were assessed using validated questionnaires. Noise levels were recorded on court using stationary sound level meters, and individual noise exposure was measured using personal carried noise dosimeters. The results showed a statistically significant correlation between spectator noise level and stress, mainly when umpires were working as service judge. Umpires with a higher subjective sensitivity to noise and higher general stress levels showed a stronger correlation between noise levels and stress during matches. The findings suggest that spectator noise may be a factor to consider in efforts to support umpire performance and well-being in stressful environments. Further research is needed to investigate the potential impact of this association on decision-making processes.